Penerapan Building Information Modeling (BIM) Dalam Peningkatan Efisiensi Biaya Dan Jadwal Pada Proyek Konstruksi Gedung Bertingkat Tinggi - Andres (CV. SINAR HOWUHOWU, 2025)
This study analyzes the application of Building Information Modeling (BIM) as a solution to enhance cost and schedule efficiency in high-rise building construction projects. While such projects often face challenges of cost overruns and delays, this research demonstrates that the adoption of BIM fundamentally transforms project management into a more integrated and efficient process. A qualitative approach with a case study method was used to collect primary data through in-depth interviews and secondary data from project documents. The findings indicate that BIM significantly contributes to cost efficiency through more accurate estimations (5D BIM), reduced material waste, and minimal rework. In terms of schedule, BIM accelerates the construction process with virtual clash detection at early stages (4D BIM), which reduces delays on-site. Furthermore, BIM improves team collaboration and facilitates faster decision-making. Although initial adoption requires investment, its long-term benefits, such as financial savings and project acceleration, far outweigh the costs. This study concludes that BIM is a transformative methodology crucial for achieving success in modern construction projects.